2022
DOI: 10.1055/s-0042-1757568
|View full text |Cite
|
Sign up to set email alerts
|

Trueness and Precision of Eight Intraoral Scanners with Different Finishing Line Designs: A Comparative In Vitro Study

Abstract: Objective This study aimed to evaluate the accuracy in terms of trueness and precision of eight intraoral scanners (IOS) and the effect of different finishing line designs on the IOS's accuracy. Materials and Methods Three printed models of the maxillary arch with maxillary right first molar virtually prepared with chamfer, shoulder, and vertical preparation designs were used as master models in this study. Each model was scanned 30 times with each IOS: Medit i700, Planscan Emerald S, CEREC Primescan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 25 publications
(59 reference statements)
0
7
0
Order By: Relevance
“…In this study, the accuracy of IOSs was evaluated using trueness, as it illustrates the extent to which the scanned data matches reality. Several studies have utilized laboratory scanners as a reference to evaluate the trueness of IOSs by producing a standard reference model (20,27). Laboratory scanners are renowned for their enhanced precision, as they utilize structured light or lasers and are not solely optical.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…In this study, the accuracy of IOSs was evaluated using trueness, as it illustrates the extent to which the scanned data matches reality. Several studies have utilized laboratory scanners as a reference to evaluate the trueness of IOSs by producing a standard reference model (20,27). Laboratory scanners are renowned for their enhanced precision, as they utilize structured light or lasers and are not solely optical.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the statistically nonsigni cant differences between Primescan and Medit i700, the highest trueness was recorded by Primescan, which is in accordance with other studies (27)(28)(29)(30). Falih and Majeed evaluated the trueness and precision of eight IOSs on a printed model and found that Medit i700 showed greater trueness than Primescan and Trios3 (20). The differences in results between studies could be attributed to differences in the type of substrate and its optical characteristics and the metrology software used (31).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The results of the present study came in agreement with Schmidt et al, (2020) [23] who tested trueness using Trios4Pod, and Primescan intraoral scanners. Also the results of (Falih & Majeed, 2022) [6] who tested trueness using Medit i700 and Primescan extra oral scanners. Further, our results disagreed with (Lo Giudice et al, 2022) [13] who claimed that since in vivo may generate more errors than an in vitro one because clinical variables are eliminated in the in vitro process removing external factors as the patient mouth environment starting from saliva, limited mouth opening, movement of the patient, tongue and check.…”
Section: Discussionmentioning
confidence: 99%